Postpartum obesity and weight gain among human immunodeficiency virus‐infected and human immunodeficiency virus‐uninfected women in South Africa. Issue 3 (13th January 2020) - Bengtson, Angela M.; Phillips, Tamsin K.; le Roux, Stanzi M.; Brittain, Kirsty; Buba, Allison; Abrams, Elaine J.; Myer, Landon
Abstract: In South Africa, up to 40% of pregnant women are living with human immunodeficiency virus (HIV), and 30–45% are obese. However, little is known about the dual burden of HIV and obesity in the postpartum period. In a cohort of HIV‐uninfected and HIV‐infected pregnant women initiating antiretroviral therapy in Cape Town, South Africa, we examined maternal anthropometry (weight and body mass index [BMI]) from 6 weeks through 12 months postpartum. Using multinomial logistic regression, we estimated associations between baseline sociodemographic, clinical, behavioural, and HIV factors and being overweight–obese I (BMI 25 to <35), or obese II‐III (BMI >35), compared with being underweight or normal weight (BMI <25), at 12 months postpartum. Among 877 women, we estimated that 43% of HIV‐infected women and 51% of HIV‐uninfected women were obese I‐III at enrollment into antenatal care, and 51% of women were obese I‐III by 12 months postpartum. On average, both HIV‐infected and HIV‐uninfected women gained, rather than lost, weight between 6 weeks and 12 months postpartum, but HIV‐uninfected women gained more weight (3.3 kg vs. 1.7 kg). Women who were obese I‐III pre‐pregnancy were more likely to gain weight postpartum. In multivariable analyses, HIV‐infection status, being married/cohabitating, higher gravidity, and high blood pressure were independently associated with being obese II‐III at 12 months postpartum. Obesity during pregnancy is a growing public health concern in low‐ and middle‐income countries, including South Africa. Additional research to understand how obesity and HIV infection affect maternal and child health outcomes is urgently needed.